Using a Climate Change Risk Perceptions Framing to Identify Gaps in Climate Services - Steynor, Anna; Pasquini, Lorena (Frontiers in Climate, 2022)
Given the rise in climate services for decision-making, it is important to understand whether these services are meeting the context-specific needs of decision-makers, including identifying any gaps in current climate services. This study sets out to investigate the efficacy of current climate services provision in east Africa through the lens of climate change risk perceptions. Risk perceptions have established relationships with important aspects of the decision context and have been shown to influence the kinds of information people use in making decisions, therefore, an understanding of how elements of risk perceptions relate to climate services use can provide valuable insights for enhancing climate services. Using this premise, the relationships between determinants of climate change risk perceptions and the use of climate services information are explored through a combination of statistical survey analysis and qualitative interview analysis. The analysis revealed three main gaps in climate services in east Africa. These gaps include the lack of long-term climate change projections disseminated through National Meteorological Services (NMS), limited locally ground-truthed delivery of impact-based forecasts and the requirement for specialist capacity to use some complex climate services. Filling these gaps will require enhanced collaboration between the NMS, other providers of climate-related information (such as research institutes) and the practitioner and user communities in order to facilitate the coordinated delivery of locally ground-truthed impact-based forecasts, facilitate capacity development across the user-producer spectrum and augment the role of the NMS as conduits of climate change information.